Creating 12‐lead electrocardiogram waveforms using a three‐lead bedside monitor to ensure appropriate monitoring - Yoneyama, Kihei (J Arrhythm, 2020)
How do you place the three electrodes to create waveforms for leads I, II, III, aVR, aVL, aVF, and V1‐V6?[Image: see text]